Flow Injection Electrochemical Quartz Crystal Microbalance with ICP-OES Detection: Recovery of Silver by Electrodeposition with Redox Replacement in a Flow Cell. Issue 5 (24th May 2021) - Molina, Daniel E; Wall, Nathalie; Beyenal, Haluk; Ivory, Cornelius F.
Abstract : We developed a new on-line hyphenated flow injection analysis technique (FI-EQCM-ICP-OES) that allows electrochemical deposition and stripping with mass detection and elemental analysis. This technique was used to study a new system for electrochemical recovery of silver from a 0.5 mM Ag + /5 mM Cu 2+ /0.5 M H2 SO4 solution by pulsed electrodeposition with redox replacement (EDRR) in a small flow cell. The metal ions in a 500 μ l sample are injected into the sulfuric acid carrier stream and deposited onto an electrochemical quartz crystal microbalance (EQCM) electrode housed in a 50 μ l flow cell. The deposits are subsequently stripped off electrochemically in the same cell and analyzed downstream in an ICP-OES. The stripped metal layer was found to be composed of Ag with no detectable Cu for a redox replacement time of 10 s, and 91 wt.% Ag–9 wt.% Cu for a redox replacement time of 5 s. Microscopy measurements demonstrated that the electrode was covered with silver particles, some of which contain Cu in the case of the 5 s replacement time. This technique allowed the study of mass changes on the electrode during electrodeposition and open circuit times in each EDRR cycle in flowing solutions.